2020
DOI: 10.1177/0269215520918631
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a core stabilization training program on balance ability in persons with Parkinson’s disease: a randomized controlled trial

Abstract: Objective: To explore the effects of an eight-week core stability program on balance ability in persons with Parkinson’s disease. Design: Randomized controlled trial. Setting: A local Parkinson’s association. Subjects: A total of 44 participants with a clinical diagnosis of Parkinson’s disease were randomly assigned to an experimental ( n = 22) or control group ( n = 22). Intervention: The experimental group received 24 sessions of core training, while the control group received an intervention including activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 42 publications
1
22
0
1
Order By: Relevance
“…Two high-quality studies 92 , 97 compared core strengthening with conventional physical therapy, with conflicting findings related to balance. Therefore, no definitive statement can be made.…”
Section: Balance Training ♦♦♦♦mentioning
confidence: 99%
“…Two high-quality studies 92 , 97 compared core strengthening with conventional physical therapy, with conflicting findings related to balance. Therefore, no definitive statement can be made.…”
Section: Balance Training ♦♦♦♦mentioning
confidence: 99%
“…In PD however there is impaired integration of proprioception [ 9 , 10 ] which may alter the perception of an abnormal trunk position. To compensate for this, postural control in PD becomes increasingly dependent upon trunk muscle strength [ 11 ] and visual information [ 12 ]. The latter reflects increased visual dependency, which involves a shift to more reliable sensory cues, i.e., to visual afferents.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 7,394 records were retrieved from electronic databases and two additional records were obtained from other sources, of which 384 studies remained after removing duplicates and screening titles and abstracts. Based on the full-text screening, 46 records fulfilled the eligibility criteria and thus were included for qualitative analysis (i.e., systematic review), whereas seven studies were additionally excluded from the quantitative analysis (i.e., network meta-analysis) due to data not being reported and not irretrievable (Kim and Lockhart, 2010 ; Okubo et al, 2019 ; Wang et al, 2019 ), exercise types not included in the network (Allin et al, 2020 ; Cabrera-Martos et al, 2020 ), exercise intervention included in only one trial (Lacroix et al, 2016 ), and no continuous data reported (Beling and Roller, 2009 ), resulting in a total of 39 studies for NMA. The schematic flow chart for the selection process is presented in Figure 1 , and all included studies are listed in Supplementary Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Data from a total of 39 studies ( n = 1388, age = 71.5 ± 3.9 years) were included in the NMA. Of the 15 exercise types reported in Table 1 , 14 types were included in the NMA as functional training was implemented in only one study and consequently included in a disconnected network (Cabrera-Martos et al, 2020 ). There were 11 multi-arm trials, and three of which consisted of two groups sharing the same exercise type and the third group with another type (Hatzitaki et al, 2009 ; Ni et al, 2014 ; Lacroix et al, 2016 ); thus, data in these two groups were combined into a single group.…”
Section: Resultsmentioning
confidence: 99%